Researcb on Private IP Address Mutiplexing in Mobile PS Domain - Hui Xiao; Jinchao Lin; Weihua Cao; Wenyun Li (Dianxin kexue)
With the rapid development of mobile internet, a large number of IP address is consumed because most of mobile terminal is always online. Class A private IP address（10.0.0.0／8）are not adequate for large-scale operators any more. A new method was proposed which was by means of integrated carry gateway. The method can multiplex the private IP address of 10 segments, in order to solve shortage of IPv4 address before IPv6 will have been used in large-scale commercial.